Recent Routes in Synthesis and Biological Activity of Pyrimido[4,5-b] Quinoline Derivatives: A Review (Part II) - Abu-Hashem, Ameen A.; Hakami, Othman; Amri, Nasser; Ameen, Tahah A.; Bajaber, Majed A.; Youssef, Mohammed M.; Gouda, Moustafa A. (Mini-Reviews in Organic Chemistry, 2025)
The synthesis of organic molecules has been a tremendous and rapid advance in the recent decade to obtain high biological and pharmacological activities. In this review, the organic synthesis of pyrimido[4,5-b]quinoline derivatives is considered an alternative method to traditional procedures for treating many diseases that affect humans. Also, by transferring electrons, stereoselective syntheses occur via organic reactions in various unnatural and natural conditions at room temperature and normal pressure. We found that the structure of pyrimido[4,5-b]quinoline derivatives was formed by substrates, bases, electrophiles, and low-level and highly stable reagents that can be broadly applied to synthesize more heterocycles. These reagents include: 2-nitrobenzaldehyde; 3-(benzyloxy)-4-methoxy-2-nitrobenzaldehyde; 4,5-dimethoxy-2-nitrobenzal-dehyde; 2-aminobenzaldehyde; 2-aminoquinoline-3-carboxamide; 2-chloroquinoline-3-carbal-dehyde; 2-bromobenzaldehyde; 2-chloroquinoline-3-carbonitrile; 2-chloroquinoline-3-carboxylic acid; aniline; phenyl-methanamine; amino-quinoline-3-carboxylic acid /amino-quinoline-carbonitrile; amino-6,7-dimethoxy-quinoline-3-carbonitrile; amino-oxolo [4,5-g]quinolin-carboxamide; 3-(aminomethyl) quinolin-2-amine; 4-aminobenzo[d][1,3] dioxole-5-carbaldehyde; thiourea; ethyl 3-oxo-butanoate; 2-cyano-acetamide; 2-(bis (methylthio) methylene) malononitrile; ethyl 3,3-diamino-2-cyanoacrylate; naphthalene-1,4-dione; and N-carbamoyl-2-cyanoacetamide derivatives. The prepared pyrimido[4,5-b]quinoline derivatives were described through means of the following chemical reactivity: alkylation, bromination, chlorination, cyclocondensation, cyclization, acylation, oxidation-reduction, dehydration, addition reaction and Vilsmeier-Haack reaction (Vilsmeier reagent).
Keywords: 1; 2; 4-triazolopyrimidine